“You’ll lose it if you talk about it”: Brett as Relic, Pedro Romero as Peter of Rome, and the Bullfight as Carnivalesque Mass in The Sun Also Rises - Watson, James (Christianity & literature, 2017)
By tracing the often hidden presence of the Roman Catholic sacraments throughout Hemingway’s first novel, a pattern of action in priority to words emerges. Jake likes the silent, “dim” Spanish churches; so too Hemingway likes his newfound religion—one whose theology affirms that the nearest approach to God comes not by way of propositional language or spiritual meditation, but by the eating of His body in the Eucharist. This bypassing of referentiality in favor of direct and physical union puts Hemingway’s nascent “Iceberg theory” in prescient conversation with Derrida’s monumental critique of signs as vehicles of presence.